FAKTOR-FAKTOR MEMENGARUHI PURCHASE INTENTION PENONTON SHOPEE LIVE SKINTIFIC DI JAKARTA MELALUI SWIFT GUANXI - MULYANI, MELITA AURYN; HARYANTI, DENNY SEPTA (E-Jurnal Manajemen Trisakti School of Management (TSM), 2024)
The aim of this study was to determine the effect of perceived expertise, perceived similarity, perceived familiarity, perceived likeability, and swift guanxi on purchase intention in Skintific’s Shopee Live audience in Jakarta. This study uses descriptive and causality research with a 5-point Likert scale measurement. This study uses primary data obtained from questionnaires distributed through Google Form with 326 respondents. The statistics method used in this research is Structured Equation Modeling (SEM) with the SmartPLS 4.0 program. The results showed that perceived expertise, perceived similarity, perceived familiarity, and perceived likeability have effect on swift guanxi. Swift guanxi has effect on purchase intention. Swift guanxi has a mediating effect on perceived expertise, perceived similarity, perceived familiarity, and perceived likeability on Purchase Intention in Skintific’s Shopee Live audience in Jakarta.